Exon-Skipping Oligonucleotides Restore Functional Collagen VI by Correcting a Common COL6A1 Mutation in Ullrich CMD - Sara Aguti; Véronique Bolduc; Pierpaolo Ala; Mark Turmaine; Carsten G. Bönnemann; Francesco Muntoni; Haiyan Zhou (Elsevier, 2020)
Collagen VI-related congenital muscular dystrophies (COL6-CMDs) are the second most common form of congenital muscular dystrophy. Currently, there is no effective treatment available. COL6-CMDs are caused by recessive or dominant mutations in one of the three genes encoding for the α chains of collagen type VI (COL6A1, COL6A2, and COL6A3). One of the most common mutations in COL6-CMD patients is a de novo deep intronic c.930+189C > T mutation in COL6A1 gene. This mutation creates a cryptic donor splice site and induces incorporation of a novel in-frame pseudo-exon in the mature transcripts. In this study, we systematically evaluated the splice switching approach using antisense oligonucleotides (ASOs) to correct this mutation. Fifteen ASOs were designed using the RNA-tiling approach to target the misspliced pseudo-exon and its flanking sequences. The efficiency of ASOs was evaluated at RNA, protein, and structural levels in skin fibroblasts established from four patients carrying the c.930+189C > T mutation. We identified two additional lead ASO candidates that efficiently induce pseudo-exon exclusion from the mature transcripts, thus allowing for the restoration of a functional collagen VI microfibrillar matrix. Our findings provide further evidence for ASO exon skipping as a therapeutic approach for COL6-CMD patients carrying this common intronic mutation.